2011
DOI: 10.1186/1471-2431-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Compliant gluten-free children with celiac disease: an evaluation of psychological distress

Abstract: BackgroundChildren with chronic illnesses are known to have increased risks for emotional and behavioral problems. In the present study, children and adolescent suffering from celiac disease (CD) were compared with healthy controls to assess differences in the psychological profile.MethodsA total of 100 well-treated and compliant CD patients (65 females/35 males; age mean ± SD: 10.38 ± 2.71) were compared to 100 normal controls (58 females/42 males; age mean ± SD: 11.47 ± 2.61). Emotional and behavioral proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 33 publications
2
69
2
8
Order By: Relevance
“…In addition, the strict gluten‐free diet effective in the treatment of celiac disease could adversely influence patients’ health‐related quality of life (Almagro, Almagro, Ruiz, González, & Martínez, ; McAllister, Williams, & Clarke, ), especially for adolescents (Mazzone et al., ). The permanent dietary restriction and vigilant monitoring necessary can foster preoccupation with, and anxiety about eating, potentially increasing the risk for pathological eating behaviors (Arigo, Anskis, & Smyth, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strict gluten‐free diet effective in the treatment of celiac disease could adversely influence patients’ health‐related quality of life (Almagro, Almagro, Ruiz, González, & Martínez, ; McAllister, Williams, & Clarke, ), especially for adolescents (Mazzone et al., ). The permanent dietary restriction and vigilant monitoring necessary can foster preoccupation with, and anxiety about eating, potentially increasing the risk for pathological eating behaviors (Arigo, Anskis, & Smyth, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that children and adolescents with CD may have emotional and behavioural problems (104) . Most CD patients showed significantly higher scores of anxiety, harm avoidance, separation panic and somatic complaints, even after the introduction of dietary regimens.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…Adherence and self-advocacy are particularly problematic for adolescents as they venture outside of the home and become more independent (13,14) . The focus on food and eating behaviours, and possibly even adherence to a GFD, may be associated with an increased risk of psychosocial problems and disordered eating patterns and behaviours in adolescents with CD (15)(16)(17)(18)(19)(20)(21) .…”
Section: Introductionmentioning
confidence: 99%